Isomorphism and Institutional Control in a Modular Plant of the Automotive Industry - Sacomano Neto, Mário; Truzzi, Oswaldo Mário Serra; Kirschbaum, Charles (Review of Business Management, 2013)
Several studies have addressed how forms of coordination are conditioned by social mechanisms such as trust, reciprocity, control, cooperation and copying. This level of analysis is a critique of the utilitarian tradition, which assumes economic behavior is only minimally affected by relationships and social structure. On the other hand, from the institutional perspective and in economic sociology, economic behavior is embedded in social relations, in which control, isomorphism and the homogeneity of organizational forms are present. In this sense, this article examines how isomorphism (mimetic, normative and coercive) and the ability to control support a cohesive and stable coordinating structure in a modular plant belonging to the automotive industry. By combining isomorphism and control, we combine two institutional field perspectives that are differente but complementary: 1) the first field perspective, understood as the total number of relevant actors, where shared meanings are built; and 2) the second field perspective, understood as an institutional sphere of interests which includes power struggles. Research is exploratory, descriptive, based on case studies and interviews with the automaker’s production director and with another two modular suppliers’ production directors. Some research results show how the automaker employs highly institutionalized mechanisms and routines that are capable of controlling and homogenizing the behavior and performance of parts suppliers. These mechanisms are not limited merely to the formal aspects of relationships, but also to its informal aspects (relationships, trust, rules, etc), capable of institutionalizing various production practices and of stabilizing relationships within the coordination of plant activities. The article points to the paradox of the socially embedded agency, to control and to homogeneity present in interorganizational relationships. The article also contributes to the understanding of how socially embedded aspects are present in coordination processes between companies.